Secondary Rhinoplasty: Aesthetic and Functional Concerns. Issue 3 (August 2019) - Loghmani, Shahriar; Loghmani, Alireza; Maraki, Fatemeh
Background: Aesthetic and functional concerns, especially after multiple revision rhinoplasties, continue to provide a challenge even for the experienced surgeon. Objective: This study aimed to report the results in terms of "secondary rhinoplasty, " performed by the senior author after previous rhinoplasty. Methods: This descriptive prospective study was carried on 150 patients with surgical indication of secondary rhinoplasty and they were asked to fill out the questionnaire divided into 3 parts: overall epidemiological questions, questions of patients' aesthetic and functional complaints, and objective evaluation by the surgeon. The nasal problems in the upper and middle regions were divided into high or low, broad or narrow, crooked, irregularity of nasal bridge, or other alterations. The patients included in the study had surgical programming of secondary rhinoplasty, with mandatory aesthetic and optional functional purposes, having previous rhinoplasty with the same or different surgeon. Results: There were 136 females and 14 males with the mean age of 31.52 (6.36) years. The most common complaints were related to the nose tip with 123 cases included deviated tip and pinched (bilateral) with 25.3%, 30.7%, and 25.3%, middle nose with 78 cases included mid vault deviation, inverted V, and polly beak with 31.3%, 18%, and 9.3%, and upper nasal region with 69 cases included dorsum irregularity and wide dorsum with the rates of 22.7% and 16.7%, respectively; respiratory problem was reported in 13 cases. Conclusion: Unilateral or bilateral twisting at the nasal tip had the highest percentages, and the lowest incidence was in relation to the complaints of the upper nasal part.